Fine-Tuning Reception in the Bone: PPARγ and Company - Z. Elizabeth Floyd; Sanjin Zvonic; Mark E. Nuttall; Jeffrey M. Gimble (PPAR Research)
PPARγ plays a central role in the formation of fat. Regulation of PPARγ activity depends on numerous factors ranging from dietary ligands to nuclear hormone coactivators and corepressors to oxygen-sensing mechanisms. In addition, the interplay of PPARγ with other nuclear hormone receptors has implications for the balance between adipogenesis and osteogenesis in mesenchymal stem cells of the bone marrow stroma. This review will explore a range of factors influencing PPARγ activity and how these interactions may affect osteogenesis.